SYSTEMIC AND CULTURAL PROTECTION OF PRIVACY IN SERBIA: TOWARDS A COMPREHENSIVE LAW IN A TRANSITIONAL CONTEXT: - - Matic, Goran (Serbian political thought, 2026)
This paper examines the normative, institutional, and cultural framework for privacy protection in the Republic of Serbia, focusing on the challenges of artificial intelligence and digital transformation. The core assumption is that current regulation fails to provide comprehensive and sustainable protection of privacy as a fundamental right. The methodology relies on normative, comparative, and critical analysis of constitutional provisions, legislation, institutional reports, and practice. Results reveal legal fragmentation, weak implementation, and limited public and institutional awareness. The conclusion emphasises the need for constitutional reform, the adoption of a systemic privacy law, and the development of cultural infrastructure to protect digital dignity.